The Relationship Between Attitude, Belief, Experience, and Knowledge of Iranian Nurses Toward the Use of Personal Protective Equipment: A Cross-Sectional Study - Zhina Banafshi; Sina Valiee; Yousef Moradi; Salam Vatandost (Wolters Kluwer Medknow Publications, 2024)
Background: Utilizing Personal Protective Equipment (PPE) is pivotal in averting infection transmission to both patients and nurses. The attitude of nurses is a critical determinant in their compliance with PPE usage. This study seeks to explore the correlation between the attitudes of Iranian nurses and their beliefs, experiences, and knowledge concerning the application of PPE. Materials and Methods: In this cross-sectional study, 303 nurses employed in hospitals affiliated with Kurdistan University of Medical Sciences (Iran) were chosen using a quota sampling technique. Between April and June 2022, they completed self-administered questionnaires, which consisted of a Demographic Information form and a four-part questionnaire on "Attitude, Belief, Experience, Knowledge" concerning the utilization of PPE. Data were analyzed utilizing descriptive and inferential statistical methods. The multiple linear regression model was applied to investigate the relationship between attitude scores and various examined variables. Results: The findings indicated that most participants held bachelor's degrees (93.07%), and their attitude scores toward using PPE exceeded 3.25 out of 6 for all 12 questions. Female gender, increased work experience, and higher organizational positions exhibited positive and significant associations with a favorable attitude toward PPE utilization. Conversely, the absence of training related to PPE, a lack of belief in infection control, and limited knowledge displayed negative correlations. Conclusions: Nurses have an ethical obligation to adhere to infection control guidelines, including consistently utilizing PPE, regardless of the level of infection risk or the visibility of the infection. Continuous training and regular monitoring of nurses in this context are indispensable.